From Margin to Authority: Islamic Legal Discourse on Women’s Political Rights in a Global Human Rights Framework - Mulyo, Mufrod Teguh; Jandra , Mifedwil; Munifah (Al-Manahij: Jurnal Kajian Hukum Islam, 2025)
This article examines the protection of women’s political rights in Islam concerning international human rights conventions. While numerous studies have addressed the historical evolution of women’s political participation, limited attention has been given to the normative foundations of Islamic teachings supporting such rights. This study seeks to fill that gap by focusing on how Islamic values uphold and safeguard women’s political rights. Employing a legal-normative approach, the research examines classical and contemporary legal literature and religious interpretations, particularly referring to the Qur’an Surah Al-Mumtahanah (60:12) as key textual evidence. The findings reveal that Islamic teachings not only permit but actively encourage women’s involvement in political life, challenging conservative interpretations that limit their participation under religious pretexts. This research contributes to scholarly discourse by fostering reconciliation between Islamic principles and global human rights standards, promoting a more inclusive and empowering view of women in Muslim societies. It also refutes prevalent misconceptions regarding Islam’s stance on women’s political engagement. Future studies are encouraged to conduct comparative analyses of how women’s political rights are implemented across diverse Islamic and non-Islamic socio-political contexts.